A positive electrode material and preparation method thereof, a pole piece, a battery and electrical equipment

By constructing Cu-Fe alloy and graphene oxide cladding on the surface of the positive electrode material of lithium-ion batteries, the structural stability and safety issues of existing positive electrode materials are solved, and the performance improvement of lithium-ion batteries with high conductivity and long life is achieved.

CN120184226BActive Publication Date: 2025-09-02PHYLION BATTERY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510646271.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-20
Publication Date
2025-09-02
Estimated Expiration
2045-05-20

AI Technical Summary

Technical Problem

The existing positive electrode materials have problems such as poor structural stability, high risk of thermal runaway, insufficient conductivity and insufficient mechanical strength in lithium-ion batteries, which cannot meet the needs of high energy density, high safety and long cycle life.

Method used

A positive electrode material adopts a core-shell composite structure, in which the core of the active material is coated with Cu-Fe alloy dopant coating, combined with graphene oxide and perfluorinated pentacene organic particle coating, enhances the conductivity and structural stability of the material, and captures oxygen atoms to reduce the risk of thermal runaway.

Benefits of technology

It significantly improves the conductivity, cycling performance and safety of lithium-ion batteries, extends battery life, reduces the risk of thermal runaway, and enhances the structural stability and mechanical strength of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120184226B_ABST
    Figure CN120184226B_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode material, a preparation method thereof, a pole piece, a battery, and electrical equipment, relating to the field of lithium-ion batteries. The positive electrode material comprises a core-shell composite structure; the core of the core-shell composite structure comprises an active material, and the core is coated with a dopant coating; the dopant coating comprises an alloy coating, and the alloy coating comprises a Cu-Fe alloy. The positive electrode material improves the battery's electrical conductivity and cycle performance, and enhances structural stability and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a positive electrode material and a preparation method thereof, a pole piece, a battery and electrical equipment. Background Art

[0002] Lithium-ion batteries, as highly efficient energy storage and conversion devices, play a vital role in modern electronic devices, electric vehicles, and energy storage systems. With increasing demands for energy efficiency and safety, optimizing the performance of lithium-ion batteries has become a research hotspot. As a core component of lithium-ion batteries, cathode materials directly influence the battery's energy density, cycle stability, and safety.

[0003] In existing technologies, cathode materials typically utilize a single active substance, such as lithium cobalt oxide (LCO) or lithium iron phosphate (LFP). While these materials offer high energy density, they suffer from poor structural stability and the risk of thermal runaway over long-term cycling, leading to rapid degradation of battery performance and potentially even safety incidents. Furthermore, existing cathode materials exhibit insufficient electrical conductivity under high-rate charge and discharge conditions, making them incapable of meeting the demands of rapid charge and discharge.

[0004] Another drawback of existing technologies is that the cathode material is prone to oxygen atom release during the charge and discharge process. This not only reduces the battery's energy efficiency but can also trigger chemical reactions within the battery, increasing the risk of thermal runaway. Furthermore, the cathode material's insufficient mechanical strength prevents the battery from expanding and contracting during charge and discharge, leading to structural damage and shortening the battery's cycle life.

[0005] In summary, existing cathode materials suffer from poor structural stability, high risk of thermal runaway, insufficient electrical conductivity, and insufficient mechanical strength. These issues hinder the development of lithium-ion batteries with high energy density, enhanced safety, and long cycle life. Therefore, developing new cathode materials to improve structural stability, safety, and electrical conductivity, reduce oxygen atom escape, and enhance mechanical strength has become a pressing challenge in lithium-ion battery technology.

[0006] In view of this, the present invention is proposed. Summary of the Invention

[0007] The first purpose of the present invention is to provide a positive electrode material, a preparation method of the positive electrode material, a method, a pole piece, a battery and electrical equipment. The positive electrode material improves the electrical conductivity and cycle performance of the battery, enhances the structural stability and safety, thereby improving the overall performance and safety of the battery.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are adopted:

[0009] In a first aspect, the present invention provides a positive electrode material, wherein the positive electrode material is a core-shell composite structure; in the core-shell composite structure, the core is an active material, and the core is coated with a dopant coating layer;

[0010] The dopant coating layer includes an alloy coating;

[0011] The alloy cladding includes a Cu-Fe alloy.

[0012] In an optional embodiment, the mass fraction of the Cu element in the Cu-Fe alloy is 15 wt %.

[0013] In an optional embodiment, the dopant coating layer has at least one of the following characteristics:

[0014] A. The substances in the dopant coating layer are all in granular form;

[0015] B. The thickness of the dopant coating layer is 1 nm to 10 nm;

[0016] C. The mass fraction of the dopant coating layer in the positive electrode material is 0.1 wt% to 5 wt%.

[0017] In an optional embodiment, the dopant coating layer further includes an organic particle coating;

[0018] The organic particle coating includes graphene oxide and perfluorinated pentacene.

[0019] In an optional embodiment, in the organic particle coating, the mass ratio of graphene oxide to perfluorinated pentacene is (60-80):(20-40).

[0020] In an optional embodiment, the mass ratio of the organic particle coating to the alloy coating is (30-60):(40-70).

[0021] In a second aspect, the present invention provides a method for preparing the positive electrode material as described in any of the aforementioned embodiments, comprising:

[0022] The iron powder and the copper powder are mixed and subjected to a ball milling process, a press forming process and a first sintering process in sequence to obtain a Cu-Fe alloy;

[0023] Mixing the Cu-Fe alloy and an active material to obtain a mixture; or mixing the Cu-Fe alloy, graphene oxide, perfluorinated pentacene and an active material to obtain a mixture;

[0024] performing a second sintering process on the mixed material to obtain the positive electrode material;

[0025] In an optional embodiment, the ball milling treatment time is 2 hours to 8 hours;

[0026] In an optional embodiment, the pressure of the press forming process is 5t~10t;

[0027] In an optional embodiment, the sintering temperature of the first sintering treatment is 900° C. to 1500° C.;

[0028] In an optional embodiment, the sintering time of the first sintering treatment is 4 hours to 12 hours;

[0029] In an optional embodiment, the sintering temperature of the second sintering treatment is 100° C. to 300° C.;

[0030] In an optional embodiment, the sintering time of the second sintering treatment is 1 hour to 2 hours.

[0031] In a third aspect, the present invention provides a pole piece, comprising the positive electrode material as described in any one of the aforementioned embodiments; or the positive electrode material prepared by the method for preparing the positive electrode material as described in any one of the aforementioned embodiments.

[0032] In a fourth aspect, the present invention provides a battery comprising the electrode as described in the aforementioned embodiment.

[0033] In a fifth aspect, the present invention provides an electrical device comprising the battery as described in the aforementioned embodiment.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The present invention provides a positive electrode material, a preparation method thereof, a pole piece, a battery, and electrical equipment. The positive electrode material significantly improves the battery's electrical conductivity and cycling performance by constructing a dopant coating layer composed of a metal alloy (Cu-Fe alloy) on the outer surface of a core active material.

[0036] The high mechanical strength of the Cu-Fe alloy significantly enhances the structural stability and safety of the material. In addition, graphene oxide can effectively capture oxygen atoms released from the positive electrode material, reducing the negative impact of oxygen atom release on battery performance.

[0037] The cathode material design of this invention optimizes the core-shell structure and achieves multiple technical advantages by constructing a dopant coating on the outer surface of the active material. This design not only improves the overall performance and lifespan of the battery, but also provides a new cathode material solution with high safety and stability for lithium-ion battery technology.

[0038] In summary, the positive electrode material and its preparation method, electrode, battery and electrical equipment of the present invention significantly improve the conductivity, cycle performance, structural stability and safety of the battery by constructing a dopant coating layer composed of Cu-Fe alloy on the outer surface of the active material, providing important technical support for the development of lithium-ion battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0040] Figure 1 This is a schematic diagram of the structure of the positive electrode material provided in the embodiments of the present application;

[0041] Figure 2 This is a SEM electron microscope image of the positive electrode material in Example 4 of the present application;

[0042] Figure 3 The capacity retention rate (%) of the batteries prepared in different embodiments of the comparative experimental examples of this application after 1500 cycles;

[0043] Figure 4 The cycle expansion rate (%) of the batteries prepared in different embodiments of the comparative experiment of this application after 1500 cycles;

[0044] Figure 5 The first discharge efficiency (%) results of the battery cells prepared in different embodiments in the comparative experimental examples of this application are shown.

[0045] Explanation of the main component symbols: 100-positive electrode material; 1-active material; 2-dopant coating layer. DETAILED DESCRIPTION

[0046] The embodiments of the present invention will be described in detail below with reference to the examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present invention and should not be construed as limiting the scope of the invention. Where specific conditions are not specified in the examples, the methods were performed according to conventional conditions or the conditions recommended by the manufacturer. Where the manufacturers of the reagents or instruments are not specified, they are all commercially available conventional products.

[0047] refer to Figure 1In an embodiment of the present application, a positive electrode material is provided, which is a core-shell composite structure; in the core-shell composite structure, the core is an active material, and the core is coated with a dopant coating layer; the dopant coating layer includes an alloy coating; the alloy coating includes a Cu-Fe alloy.

[0048] As described above, in the embodiments of the present application, a positive electrode material is provided. This material adopts a core-shell composite structure, in which the active material serves as the core and the outer surface is coated with a dopant coating layer. The key feature of this structure is that the dopant coating layer includes an alloy coating and an organic particle coating.

[0049] The cathode material utilizes a core-shell structure, with the active material serving as the core and providing the battery's primary electrochemical activity. This design helps protect the core material and minimizes potential side reactions from direct contact with the electrolyte, thereby improving the material's stability and cycle life.

[0050] In the dopant coating layer, the alloy coating includes a Cu-Fe alloy. A small amount of oxygen overflows from the core active material, and the alloy coating includes a portion of the Cu-Fe alloy, and a portion of the Cu-Fe alloy absorbs oxygen and reacts with oxygen under certain conditions to form a CuFe2O4 spinel compound. This can be formed in two ways:

[0051] First, during the preparation process, the Cu-Fe alloy in the dopant coating layer can absorb oxygen and form a CuFe2O4 spinel compound during the sintering process under certain sintering conditions (such as temperature, time, and oxygen-rich atmosphere). This compound further improves the structural stability of the battery, thereby extending the cycle life of the battery and significantly reducing the risk of thermal runaway.

[0052] Second, during the battery cycle, the Cu-Fe alloy absorbs the oxygen overflowing from the active material and forms a CuFe2O4 spinel compound under certain conditions.

[0053] The Cu-Fe alloy was chosen for its excellent electrical conductivity and mechanical strength. The addition of the Cu-Fe alloy not only improves the material's electrical conductivity but also enhances its structural stability.

[0054] It should be noted that the Cu-Fe alloy, as a metal coating, possesses excellent electrical conductivity. When combined with the active material, it can improve the battery's conductivity and cycling performance. Furthermore, the Cu-Fe alloy's high mechanical strength improves the material's structural stability and chemical stability, maintaining structural integrity during the battery's charge and discharge processes. This stability enables the alloy to resist corrosion and decomposition at high temperatures or in electrochemical environments, thereby reducing side reactions and improving the material's cycling and safety.

[0055] During the cycle of the battery prepared by the above-mentioned positive electrode material, oxygen atoms will escape, and the Cu-Fe alloy in the positive electrode material can capture the escaped oxygen atoms, reducing the risk of thermal runaway of the battery and further improving the safety of the battery.

[0056] Structurally, the Cu-Fe alloy provides high mechanical strength, enhancing the structural stability of the cathode material. The CuFe2O4 spinel compound offers high thermal stability and chemical inertness, reducing structural damage. The synergistic effect of the two further enhances the structural stability of the cathode material and reduces volume changes during charge and discharge.

[0057] In terms of electrical conductivity, Cu-Fe alloys offer high electrical conductivity, improving the battery's charge-discharge performance. While CuFe2O4 spinel compounds are less conductive than Cu-Fe alloys, they form a stable protective layer and reduce side reactions. The synergistic effect of these two materials improves the overall conductivity of the cathode material and reduces the battery's internal resistance under high-rate charge and discharge conditions.

[0058] From a safety perspective, the Cu-Fe alloy reduces volume expansion and contraction during charge and discharge, improving structural stability. The CuFe2O4 spinel compound, on the other hand, reduces oxygen escape and lowers the risk of thermal runaway. The synergistic effect of these two substances significantly improves battery safety and reduces the risk of thermal runaway.

[0059] In summary, the coexistence of a Cu-Fe alloy and a CuFe2O4 spinel compound in the dopant coating layer offers the best performance for batteries. This combination combines the advantages of both, improving the structural stability, conductivity, and safety of the cathode material, thereby significantly enhancing the overall performance and lifespan of the battery. These advantages make this cathode material promising for application in lithium-ion battery technology.

[0060] In some embodiments, the mass fraction of Cu element in the Cu-Fe alloy is 15 wt %.

[0061] In some embodiments, the dopant coating layer has at least one of the following characteristics:

[0062] A. The substances in the dopant coating layer are all in granular form;

[0063] B. The thickness of the dopant coating layer is 1 nm to 10 nm; for example, the thickness can be 1 nm, 2 nm, 3 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc.

[0064] C. The mass fraction of the dopant coating layer in the positive electrode material is 0.1 wt% to 5 wt%. For example, the mass fraction can be 0.1 wt%, 0.5 wt%, 0.8 wt%, 1 wt%, 3 wt%, 5 wt%, etc.

[0065] In some embodiments, the dopant coating layer further includes an organic particle coating; the organic particle coating includes graphene oxide and perfluorinated pentacene.

[0066] It should be noted that among the organic particle coatings, perfluorinated pentacene (PFP) is an n-type organic semiconductor material with high chemical stability. Therefore, it is not easily oxidized or reduced in chemical reactions and can maintain its structure and properties in various chemical environments.

[0067] The high electron affinity of perfluorinated pentacene means it easily attracts and stabilizes additional negative charges. This property enables PFP to effectively adsorb and stabilize oxygen atoms, thus providing a basis for the adhesion of graphene oxide (rGO).

[0068] The high electron affinity of perfluorinated pentacene leads to easier stabilization of the additional negative charge, providing a basis for the adhesion of graphene oxide (rGO).

[0069] Structurally, the perfluorinated pentacene molecule is a two-dimensional conjugated π-electron system, with the benzene rings matching the hexagonal structure of graphene. This structural similarity allows PFP and rGO to interact better, forming a stable interface.

[0070] The synergistic effect of rGO particles and PFP can provide better electronic conductivity. Specifically, the high electron affinity and π-electron system of PFP can interact with the conductive network of rGO, enhancing the efficiency of electron transfer.

[0071] The synergistic effect of PFP and rGO can form a more stable electrode-electrolyte interface. This stable interface helps reduce side reactions during the battery's charge and discharge process, improving the overall performance and life of the battery.

[0072] In summary, perfluorinated pentacene (PFP), a highly chemically stable n-type organic semiconductor material, can effectively adsorb and stabilize oxygen atoms through its high electron affinity and structural compatibility with graphene oxide (rGO), providing improved electronic conductivity and forming a more stable electrode-electrolyte interface. These properties make the synergistic effect of PFP and rGO of great significance in improving battery performance and safety.

[0073] In some embodiments, the weight ratio of graphene oxide to perfluorinated pentacene in the organic particle coating is (60-80):(20-40). For example, the weight ratio of graphene oxide can be 40, 45, 50, 60, 70, etc. For example, the weight ratio of perfluorinated pentacene can be 20, 25, 30, 35, 40, etc.

[0074] In some embodiments, the weight ratio of the organic particle coating to the alloy coating is (30-60):(40-70). For example, the weight ratio of the alloy coating can be 40, 45, 50, 60, 70, etc. The weight ratio of the organic particle coating can be 30, 35, 40, 50, 60, etc.

[0075] In an embodiment of the present application, a method for preparing a positive electrode material as described in any one of the aforementioned embodiments is provided, comprising:

[0076] Step S1: mixing iron powder and copper powder, and sequentially subjecting the mixture to ball milling, pressing and first sintering to obtain a Cu-Fe alloy.

[0077] Iron powder and copper powder are mixed in a certain proportion to ensure that the two are evenly distributed in preparation for forming an alloy; then ball milling is carried out. Ball milling is a mechanical alloying process used to refine powder particles and promote alloying. Specifically, the mixed iron powder and copper powder can be placed in a ball mill. Through the rotation and impact of the ball mill, the powder particles are refined and alloying begins, thereby obtaining finer powder particles, and part of the iron and copper begin to form an alloy.

[0078] Pressing is the process of pressing the milled powder into a specific shape to facilitate sintering. Specifically, the milled powder is placed in a mold and pressed by a press to form a preformed Cu-Fe alloy.

[0079] The first sintering process is a process of solidifying the pressed powder into a solid material. Specifically, the pressed Cu-Fe alloy can be sintered at a high temperature to solidify it and form a strong alloy structure.

[0080] Step S2: mixing the Cu-Fe alloy, graphene oxide, perfluorinated pentacene and active material, and performing a second sintering treatment to obtain the positive electrode material.

[0081] As mentioned above, the Cu-Fe alloy, graphene oxide, perfluorinated pentacene, and active material are mixed in a certain proportion to ensure uniform distribution. Then, a second sintering process is performed after mixing to make the materials more tightly bonded and remove impurities brought by the materials.

[0082] The positive electrode material prepared by the above method has excellent electrochemical properties and thermal stability and is suitable for use in high-performance lithium-ion batteries.

[0083] In some embodiments, the ball milling time is 2 hours to 8 hours. For example, the time can be 2 hours, 4 hours, 6 hours, 8 hours, etc.

[0084] In some embodiments, the pressure of the press molding process is 5t to 10t. For example, the pressure can be 5t, 6t, 7t, 8t, 9t, 10t, etc.

[0085] In some embodiments, the sintering temperature of the first sintering process is 900° C. to 1500° C. For example, the sintering temperature may be 900° C., 1000° C., 1100° C., 1200° C., 1300° C., 1500° C., and the like.

[0086] In some embodiments, the sintering time of the first sintering process is 4 hours to 12 hours. For example, the sintering time can be 4 hours, 6 hours, 8 hours, 12 hours, etc.

[0087] In some embodiments, the sintering temperature of the second sintering process is 100° C. to 300° C. For example, the sintering temperature can be 100° C., 150° C., 200° C., 250° C., 300° C., etc.

[0088] In some embodiments, the sintering time of the second sintering process is 1 hour to 2 hours. For example, the sintering time can be 1 hour, 1.5 hours, 2 hours, etc.

[0089] It should be noted that in this embodiment, the sintering process performed after mixing the Cu-Fe alloy, graphene oxide, perfluorinated pentacene, and active material is the second sintering process, specifically, a low-temperature sintering process. In this low-temperature sintering process, the sintering conditions employed may include a temperature of 100°C to 300°C for 1 to 2 hours.

[0090] Secondly, in this embodiment, by adopting a shorter sintering time (1 hour to 2 hours), the reaction is further limited so that the reaction does not proceed too thoroughly, thereby preventing part of the Cu-Fe alloy from being converted.

[0091] An embodiment of the present application provides an electrode sheet, comprising the positive electrode material as described in any one of the aforementioned embodiments; or the positive electrode material prepared by the method for preparing the positive electrode material as described in any one of the aforementioned embodiments.

[0092] As mentioned above, the electrode piece can be composed of a current collector and a positive electrode active layer, wherein the current collector is usually made of metal foil, which serves as a channel for electron transmission and supports the active material.

[0093] Among them, the positive electrode active layer can be made by coating a slurry formed by mixing a core-shell structured positive electrode material, a conductive agent, a binder and a solvent on a current collector, and then drying and compacting it.

[0094] A battery is provided in an embodiment of the present application, including the electrode as described in the above embodiment.

[0095] The battery described above may be a lithium-ion battery, a rechargeable battery that relies on the movement of lithium ions between the positive and negative electrodes during charging and discharging. The battery may consist of positive and negative electrode sheets, each containing corresponding active materials, a conductive agent, a binder, and a current collector. The positive electrode sheet absorbs lithium ions during discharge and releases them during charging, while the negative electrode sheet does the opposite. The electrolyte serves as an ionic conductive medium, while the separator allows lithium ions to pass while preventing direct contact between the positive and negative electrodes, which could cause a short circuit. The battery casing protects the internal components and maintains a seal, while the tabs connect the battery's internal circuitry to the external circuitry. Furthermore, a battery management system (BMS) monitors the battery status to ensure safe operation and extend battery life. This overall design enables lithium-ion batteries to provide high energy density, high power density, excellent safety performance, and a long cycle life.

[0096] An embodiment of the present application provides an electrical device, including the battery described in the aforementioned embodiment.

[0097] The aforementioned "electrical equipment" refers to any device that incorporates a battery as an energy source or component. These devices utilize batteries to power their functions. Examples include, but are not limited to, mobile phones (smartphones), laptops, electric vehicles (EVs), electric bicycles and motorcycles, portable electronic devices, medical devices, household appliances, industrial equipment, wearable devices, energy storage systems, aerospace equipment, emergency lighting, and security systems. These devices demonstrate the diverse and critical role of batteries in modern life, and the importance of high-performance batteries in improving the performance and safety of these devices.

[0098] The present invention is further described below by way of specific examples. However, it should be understood that these examples are merely provided for more detailed description and are not to be construed as limiting the present invention in any form.

[0099] Example 1

[0100] This embodiment provides a positive electrode material with a core-shell composite structure, wherein the core is an active material NCM (811), and the dopant coating layer covering the core is a Cu-Fe alloy, the mass fraction of the Cu element is 15wt%, and is referred to as Cu-15%Fe alloy in this embodiment and subsequent embodiments.

[0101] Preparation method:

[0102] (1) Preparation of Cu-15%Fe alloy: Iron powder and copper powder were mixed in a ratio of 15% by mass, ball-milled for 2 h, pressed under a pressure of 5 t, and sintered at 1000 °C for 4 h to obtain a Cu-15%Fe alloy.

[0103] (2) Cu-15%Fe alloy with a mass fraction of 1.5% and NCM(811) were mixed at high speed in a high-speed mechanical mixing device for 1 hour to obtain a mixture;

[0104] (3) The mixture was sintered at 150° C. for 1 hour to obtain the positive electrode material.

[0105] Example 2

[0106] The method used in this embodiment is basically the same as that in Example 1, except that the mass fraction of the Cu-15%Fe alloy is 0.1%.

[0107] Example 3

[0108] The method used in this embodiment is basically the same as that in Example 1, except that the mass fraction of the Cu-15%Fe alloy is 5%.

[0109] Example 4

[0110] This embodiment provides a positive electrode material with a core-shell composite structure, wherein the core is an active material NCM (811), and in the dopant coating layer covering the core, the alloy coating is a Cu-15% Fe alloy, and the organic particle coating is graphene oxide (rGO) and perfluorinated pentacene (PFP).

[0111] Preparation method:

[0112] (1) Preparation of coating layer: graphene oxide (rGO) and perfluorinated pentacene (PFP) with a mass ratio of 60:40 were prepared as organic particle coatings;

[0113] (2) Organic particle coating and Cu-15%Fe alloy were used as coating layer raw materials in a mass ratio of 40:60;

[0114] (3) The coating layer raw materials and NCM (811) were mixed at high speed in a high-speed machine for 1 hour to obtain a mixture; wherein the mass fraction of the coating layer raw materials in the total amount was 1.5%;

[0115] (4) Sintering the mixture at 150° C. for 1 hour to obtain the positive electrode material.

[0116] The cathode material obtained in this embodiment was tested by electron microscopy, and the results were as follows: Figure 2 shown.

[0117] Example 5

[0118] The method used in this embodiment is basically the same as that in embodiment 4, except that the mass fraction of the coating layer raw material in the total amount is 0.1%.

[0119] Example 6

[0120] The method used in this embodiment is basically the same as that in embodiment 4, except that the mass fraction of the coating layer raw material in the total amount is 5%.

[0121] Example 7

[0122] The method used in this embodiment is basically the same as that in Example 1, except that the mass fraction of the coating layer raw material accounts for 3% of the total amount.

[0123] Example 8

[0124] The method used in this embodiment is basically the same as that in embodiment 4, except that the mass fraction of the coating layer raw material in the total amount is 3%.

[0125] Comparative experimental example:

[0126] For the above examples and comparative examples, the following battery performance tests were conducted:

[0127] Test method:

[0128] (1) Assembling a battery: Using the positive electrode material prepared in Examples 1-8, prepare a positive electrode sheet, and prepare a negative electrode sheet (negative electrode), assemble into a bare cell, inject electrolyte, and package to obtain the lithium-ion battery to be tested corresponding to Examples 1-8.

[0129] Specific methods include:

[0130] A. The electrolyte contains organic solvents including ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC). The lithium salt is 1 mol / L lithium hexafluorophosphate, and vinylene carbonate is used as a film-forming additive. To prepare the electrolyte, mix the organic solvents in a volume ratio of 1:1:1 for EC:DMC:EMC. Dissolve 1.0 mol / L of LiPF6 and stir thoroughly. Add 5% VC and stir thoroughly to obtain the electrolyte.

[0131] B. Prepare the positive electrode sheet: Mix the prepared positive electrode material, conductive agent (Super P), and binder (PTFE) in a mass ratio of 8:1:1 to form a positive electrode slurry. Apply the positive electrode slurry onto aluminum foil, dry it, and compact it to obtain the positive electrode sheet.

[0132] C. Assemble the bare cell: Stack the positive electrode sheet, separator (polyethylene), and negative electrode sheet in sequence to form a bare cell. Squeeze the bare cell for 15 to 20 seconds, repeating five times to ensure a tight structure.

[0133] D. Inject electrolyte: Inject the prepared electrolyte into the battery cell to ensure that the electrolyte fully soaks the battery cell.

[0134] E. Packaging: Place the battery cell injected with electrolyte into the battery casing and perform vacuum packaging.

[0135] (2) The lithium-ion batteries prepared in Examples 1-8 were charged at a constant current of 1C at room temperature (25°C), discharged at a cutoff current of 0.05C, rested for 10 minutes, and then discharged at 0.7C for 1500 cycles. The capacity retention rate (%) and cycle expansion rate (%) after 1500 cycles were calculated.

[0136] The upper limit of the charge voltage is 4.0V. The pass criteria for the cycle performance test are: 1500 times capacity retention rate ≥80%, cycle expansion thickness ≤10%. The test results are shown in Table 1.

[0137] The lithium-ion batteries prepared in Examples 1-8 were subjected to formation and subsequent capacity and gas production volume tests to obtain the first discharge efficiency of the battery cells, which was calculated using the following formula:

[0138] .

[0139] Test results:

[0140] Table 1. Battery performance test results

[0141]

[0142] Result analysis:

[0143] (1) Based on the results in Table 1, and Figure 3 、 Figure 4 and Figure 5 It can be seen that the lithium-ion batteries prepared in Examples 1 to 3 and Example 7 have excellent cycle performance and initial efficiency.

[0144] (2) Compared with Example 4, Example 5 reduces the mass fraction of the coating layer to 0.1%, which has little effect on the overall electrical performance and safety performance.

[0145] (3) Compared with Example 4, the mass fraction of the coating layer raw materials in Example 6 is increased from 1.5% to 5%. It can be seen from the data in Table 1 that compared with Example 4, the electric cycle performance and first efficiency of the battery in Example 6 are significantly improved. The reason for this may be that some oxygen atoms will fall off during the cycle of the battery, and graphene oxide has the ability to capture oxygen atoms. When the content of Cu-15%Fe alloy is high, the Cu-15%Fe alloy will capture the oxygen atoms in the coating layer to generate CuFe2O4 spinel compounds.

[0146] (4) Cu-Fe alloys have a strong adsorption capacity for oxygen atoms. Among them, the surfaces of Cu and Fe can form stable chemical bonds with oxygen atoms. For example, Cu and Fe atoms on the surface of Cu-Fe alloys can form Cu-O and Fe-O bonds with oxygen atoms. The formation of these bonds helps to stabilize oxygen atoms and prevent them from escaping. From the first-principles calculation, the surface sites of Cu and Fe have high adsorption energies for oxygen atoms, which indicates that the adsorption of oxygen atoms on the surface of Cu-Fe alloys is a thermodynamically favorable process. Among them, the fcc (face-centered cubic) hollow site on the Cu(111) surface is the most stable oxygen adsorption site.

[0147] The CuFe2O4 spinel compound acts as a ceramic material layer, covering the outer surface of the active material to form a protective layer, further stabilizing the interface structure and improving the electrical performance and safety performance of the battery.

[0148] (5) Compared with Example 4, the mass fraction of the coating layer raw materials in Example 8 is increased from 1.5% to 3%, and it also has relatively excellent electrical properties and safety performance. The reasons are as described in (4) above.

[0149] (6) The cyclic expansion performance of the lithium-ion batteries prepared in Examples 1 to 3 and Example 7 is lower than that of Example 4. This may be because, although the alloy itself has high structural stability and high conductivity, it is relatively rigid and may have defects that are prone to cracking. These characteristics may be detrimental to the stability of battery expansion. However, the dopant coating layer doped with graphene oxide (rGO) and perfluorinated pentacene (PFP) can significantly improve the performance of the battery.

[0150] Specifically, the synergistic effect of rGO and PFP not only improves the conductivity of the material, but also enhances the stability of the electrode-electrolyte interface, thereby effectively reducing the volume change and structural collapse of the battery during charge and discharge, significantly reducing the cycle expansion rate, and improving the overall stability and cycle life of the battery.

[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode material, characterized in that The positive electrode material is a core-shell composite structure; in the core-shell composite structure, the core is an active material, and the core is coated with a dopant coating layer; The dopant coating layer includes an alloy coating; the mass fraction of the dopant coating layer in the positive electrode material is 0.1wt%~5wt%; The alloy coating comprises a Cu-Fe alloy; The positive electrode material is prepared by the following method: mixing iron powder and copper powder, and subjecting the mixture to ball milling, pressing and first sintering to obtain a Cu-Fe alloy; mixing the Cu-Fe alloy with an active material to obtain a mixture; and subjecting the mixture to a second sintering to obtain the positive electrode material; Among them, the ball milling time is 2 hours to 8 hours; the pressure of the press molding process is 5t to 10t; the sintering temperature of the first sintering process is 900℃ to 1500℃; the sintering time of the first sintering process is 4 hours to 12 hours; the sintering temperature of the second sintering process is 100℃ to 300℃; and the sintering time of the second sintering process is 1 hour to 2 hours.

2. The positive electrode material according to claim 1, wherein The mass fraction of the Cu element in the Cu-Fe alloy is 15 wt %.

3. The positive electrode material according to claim 1, wherein The dopant coating layer has at least one of the following characteristics: A. The substances in the dopant coating layer are all in granular form; B. The thickness of the dopant coating layer is 1 nm to 10 nm.

4. The positive electrode material according to claim 1, wherein The dopant coating layer also includes an organic particle coating; The organic particle coating includes graphene oxide and perfluorinated pentacene.

5. The positive electrode material according to claim 4, characterized in that In the organic particle coating, the mass ratio of graphene oxide to perfluorinated pentacene is (60-80):(20-40); and / or, The mass ratio of the organic particle coating to the alloy coating is (30-60):(40-70).

6. A method for preparing the positive electrode material according to any one of claims 1 to 5, characterized in that: include: The iron powder and the copper powder are mixed and subjected to a ball milling process, a press forming process and a first sintering process in sequence to obtain a Cu-Fe alloy; Mixing the Cu-Fe alloy and an active material to obtain a mixture; or mixing the Cu-Fe alloy, graphene oxide, perfluorinated pentacene and an active material to obtain a mixture; The mixed material is subjected to a second sintering process to obtain the positive electrode material.

7. The method for preparing the positive electrode material according to claim 6, wherein: The ball milling time is 2 hours to 8 hours; The pressure of the press forming process is 5t~10t; The sintering temperature of the first sintering treatment is 900° C. to 1500° C.; The sintering time of the first sintering treatment is 4 hours to 12 hours; The sintering temperature of the second sintering treatment is 100° C. to 300° C.; The sintering time of the second sintering treatment is 1 hour to 2 hours.

8. A pole piece, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 5; or the positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 6 to 7.

9. A battery, characterized in that: Comprising the pole piece as claimed in claim 8.

10. An electrical equipment, characterized in that: Comprising the battery of claim 9.

Citation Information

Patent Citations

  • Composite cathode material and preparation method and application thereof, and lithium ion battery

    CN112271279A

  • Preparation method of core-shell structure and coated lithium cobalt oxide positive electrode material

    CN114014374A